A content analysis of hand hygiene materials targeting elementary-age children. - Quilliam, E T; McKay, B A; Lapinski, M K; Viken, G; Plasencia, J; Wang, Z; Fraser, A (Health Education Research, 2018)
Millions of dollars have been spent on the design and dissemination of educational materials to improve handwashing to prevent infectious diseases. School-age children have been the focus of many of these efforts; yet little is known about the content of these materials. This study uses content analysis to examine the theoretical and motivational trends as well as the communication approach used in a sample of hand hygiene intervention materials targeting elementary-age children. Two trained coders analyzed 144 communication materials. Study results indicate that educational materials infrequently exhibit information consistent with theories of communication for behavior change, commonly use fear-based messaging, and rarely recommend using technology in the design of the interventions. Implications for future research and the design of more strategic, child-focused hand hygiene interventions are discussed.